A double condition triggered self-dissolving protective film under wading environment and a preparation method thereof
Patent Information
- Application Number
- CN202610037932.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-01-13
AI Technical Summary
但是,传统水下保护膜或离型纸需人工剥离,潜水员或机械手操作风险高、效率低,且剥离碎屑易造成二次污染
本申请的自溶型防护膜采用“涉水环境+特定机械振动”双条件触发自溶,该特定机械振动(频率为50-200Hz、振幅≥0.2mm)在涉水的自然环境中不存在,避免因水流扰动、波浪等导致的误触发,减少了防护膜的误触发概率,大幅提升了防护的针对性和可靠性;自溶触发后,分散于动态交联网络中的械敏感微胶囊破碎,释放柠檬酸-柠檬酸钠缓冲型解交联剂,高效破坏三元交联体系的硼酸酯键,促使内膜层快速溶解,避免了传统防护膜需人工清理、残留污染或自溶不彻底阻碍后续作业的问题,尤其适用于水下临时防护、精密设备表面临时保护层等需自动清除的场景;最外层的复合疏水屏障层成分安全,用量少、易降解,避免了传统防护膜材料难降解、残留污染环境的问题。
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the field of self-dissolving protective membrane technology, and in particular to a self-dissolving protective membrane triggered under dual conditions in a water-related environment and its preparation method. Background Technology
[0002] In underwater engineering, industrial manufacturing, and other fields, protective films or release papers are often used to temporarily protect underwater components, precision parts, and equipment to isolate them from impurities, corrosive media, and harmful microorganisms in the water, ensuring the performance stability and operational reliability of the protected objects. However, traditional underwater protective films or release papers require manual peeling, which is risky and inefficient for divers or robotic arms, and the peeling debris can easily cause secondary pollution.
[0003] Existing water-soluble membranes typically dissolve upon contact with water, or dissolve within a short period after contact, failing to meet the application requirements for long-term underwater storage or precise control of dissolution triggering time. Furthermore, while underwater membranes based on pH, temperature, or light signals have been reported, the complex and variable aquatic environment often renders these triggering membranes unstable and unreliable in environments with temperature fluctuations, pH fluctuations, or saline conditions, making it impossible to accurately match the protection and dissolution timing requirements of actual operations.
[0004] Therefore, developing an underwater protective membrane material that can solve the above-mentioned technical problems and has the characteristics of safe, manual-free peeling, precise and controllable dissolution, and wide environmental adaptability has become an urgent technical challenge to be solved in this field. Summary of the Invention
[0005] The purpose of this application is to provide a self-dissolving protective membrane triggered under dual conditions in a water-related environment and its preparation method, which can achieve specific mechanical triggering, rapid dissolution and zero residue removal, so as to solve or alleviate the problems existing in the prior art.
[0006] To achieve the above objectives, this application provides the following technical solution: A self-dissolving protective membrane triggered under dual conditions in a water-contaminated environment includes an inner membrane layer and a composite hydrophobic barrier layer disposed on the inner membrane layer; The inner membrane layer comprises a dynamic cross-linking network and mechanosensitive microcapsules dispersed within the dynamic cross-linking network; the dynamic cross-linking network is a ternary reversible cross-linking system composed of polyvinyl alcohol, borax, and boric acid, wherein borax accounts for 0.6-1.2 wt% of the dry weight of polyvinyl alcohol, and boric acid accounts for 0.3-1.0 wt% of the dry weight of polyvinyl alcohol; The mechanosensitive microcapsules, embedded as discrete phases within a dynamic cross-linked network, serve as the response units for mechanical vibrations. The capsule wall thickness of the mechanosensitive microcapsules is 50-200 nm, and the glass transition temperature T0 is... gThe temperature range is between -10℃ and 10℃ to ensure brittle fracture under set vibration conditions; the amount of the mechanically sensitive microcapsules added accounts for 3-8 wt% of the dry weight of polyvinyl alcohol; the swelling rate of the inner membrane layer in still water at 15-35℃ and salinity of 0-35‰ is <5%, and it can maintain structural integrity for more than 10 minutes in still water. The composite hydrophobic barrier layer is composed of a hydrophobic agent sprayed or impregnated onto the membrane surface, providing initial static water barrier; the hydrophobic agent is selected from paraffin wax, silane-modified acrylic resin, or fluorocarbon surfactant; the static water contact angle of the composite hydrophobic barrier layer is ≥110°, which can effectively block environmental water vapor and short-term water immersion; the thickness of the composite hydrophobic barrier layer is 0.5-5μm, which is easy to prepare industrially and has better water blocking effect; the composite hydrophobic barrier layer can generate microcracks under mechanical vibration with a frequency of 50-200Hz and an amplitude of ≥0.2mm, forming water molecule permeation channels.
[0007] Furthermore, the dynamic crosslinking network is based on polyvinyl alcohol with a degree of polymerization of 1700-2000 and a degree of hydrolysis of 88-99%, and is formulated into an 8-12 wt% aqueous solution, which forms a ternary reversible crosslinking system with borax and boric acid.
[0008] Furthermore, the density of the borate ester bond is 0.8-1.5 mmol / g; the molar ratio of borax to boric acid is 1:(0.5-2).
[0009] Furthermore, the microcapsules showed no rupture after immersion in still water at 25°C for 60 minutes, exhibiting extremely low leakage of the core material. The mechanosensitive microcapsules have a particle size of 1-10 μm and a D50 controlled at 3-6 μm to ensure uniform dispersion. The core of the mechanosensitive microcapsules accounts for 70-80 wt% of the total microcapsule mass and is a citric acid-sodium citrate buffered decrosslinking agent with a pH of 4.5-6.5. This decrosslinking agent contains an aqueous solution of citric acid and sodium citrate in a mass ratio of 1:(1.2-1.5). When the microcapsules rupture upon stimulation to release the core, the buffer solution acidifies the local environment, promoting the release of tetrahydroxyborate ions (B(OH)4) in the gel network. — The protons are converted into boric acid molecules (B(OH)3), thereby disrupting the dynamic equilibrium of boric acid ester bonds and causing membrane disintegration in physiological saline or freshwater environments.
[0010] The mechanosensitive microcapsules were prepared using an in-situ polymerization method. First, an aqueous solution containing citric acid and sodium citrate was prepared, and its pH was adjusted to the range of 4.5-6.5. A trace amount (<0.5 wt%) of polyvinyl alcohol was added to adjust the viscosity. Second, using cyclohexane as the continuous phase, an oil phase was prepared by adding the emulsifier Span-80 and wall-forming monomers (isophorone diisocyanate IPDI, styrene, divinylbenzene DVB, and azobisisobutyronitrile AIBN). The aqueous phase was dispersed in the oil phase under a shear rate of 1000-1500 rpm to form a water-in-oil emulsion (W / O), followed by a reaction at 65-70°C for 4-6 hours. During this process, the isocyanate at the interface reacted with water to form polyurea, and styrene underwent free radical polymerization to form polystyrene. The two components together formed a polyurea / polystyrene interpenetrating network (PU / PS IPN) capsule wall in situ, with a polyurea to polystyrene mass ratio of 1:1 in the capsule wall.
[0011] Furthermore, the total thickness of the self-dissolving protective film is 40-120μm with a tolerance of ±3μm, possessing both good mechanical strength and flexibility.
[0012] Furthermore, the mechanically sensitive microcapsules are prepared by in-situ polymerization; the composite hydrophobic barrier layer is subjected to thermosetting at 80-100℃ or UV curing treatment.
[0013] This application also proposes a method for preparing a self-dissolving protective membrane triggered under dual conditions in a water-related environment, comprising the following steps: Polyvinyl alcohol is dissolved in water at 80-90℃ to prepare a solution with a concentration of 8-12wt%. At 55-65℃, borax and boric acid are added to a polyvinyl alcohol solution and stirred for 30-40 minutes to form a ternary reversible crosslinking system. Mechanically sensitive microcapsules were added to the ternary reversible crosslinking system, and the mixture was ultrasonically dispersed and vacuum degassed to obtain a mixture. The mixture is coated into a film and dried at 78-82℃ for 10-20 minutes to obtain the inner film layer. The dried inner membrane layer is treated with a hydrophobic barrier; after curing, the self-fluxing protective membrane has a tensile strength ≥25MPa and an elongation at break ≥150%, which can meet the processing requirements such as winding and bending.
[0014] Furthermore, a composite hydrophobic barrier layer is formed by spraying or impregnating a 5-10 wt% hydrophobic agent solution and drying it at 50-60°C for 5-10 minutes. Finally, it is cured by heat curing or ultraviolet light curing. For ease of subsequent storage and transportation, the self-dissolving protective film is rolled up and stored.
[0015] The self-dissolving protective membrane is a disposable consumable. The self-dissolving trigger of the membrane simultaneously satisfies two conditions: "membrane surface in contact with water" and "mechanical vibration at 50-200Hz with an amplitude ≥0.2mm," achieving a precise match with dissolution requirements. When these two conditions are met, the mechanically sensitive microcapsules rupture, releasing a citrate-sodium citrate buffered decrosslinking agent, hydrolyzing the borate ester crosslinking bonds, causing the dynamic crosslinking network of the inner membrane layer to dissociate. Simultaneously, microcracks are generated in the hydrophobic barrier layer, introducing water and causing the membrane to completely dissociate and dissolve within 30 seconds. The dissolution product of the self-dissolving protective membrane is a polyvinyl alcohol (PVA) oligomer and borate complex, free of heavy metals or halogenated flame retardants.
[0016] In use, the self-dissolving protective film is pre-attached to the surface of the substrate to be protected, and then the vibration output end of the triggering device is brought into contact with the self-dissolving protective film to trigger it. The triggering device for the self-dissolving protective film can be an electromagnetic vibrator or a vibrating rod, and the wave frequency emitted by the triggering device is 50-200Hz and the amplitude is 0.2-1mm. The self-dissolving protective film can also be remotely triggered to dissolve using a remote triggering device. For example, a pulse square wave with a duty cycle of 30-50% and a single pulse width of 0.1-0.5s can be used for driving.
[0017] Tests showed that the self-dissolving protective membrane, when activated in a water environment with a temperature of 0-35℃, a salinity of 0-35‰, and a pH of 6-9, exhibited a dissolution rate fluctuation of no more than 10%; and the biodegradation rate of the dissolved products was ≥90% within 28 days.
[0018] The technical solution of this application has the following beneficial effects: The self-dissolving protective membrane of this application adopts a dual-condition triggering self-dissolution of "water environment + specific mechanical vibration". The specific mechanical vibration (frequency of 50-200Hz, amplitude ≥0.2mm) does not exist in the natural water environment, avoiding false triggering caused by water flow disturbance, waves, etc., reducing the probability of false triggering of the protective membrane, and greatly improving the targeting and reliability of protection. After self-dissolution is triggered, the mechanically sensitive microcapsules dispersed in the dynamic cross-linking network break down, releasing the citric acid-sodium citrate buffered de-crosslinking agent, which efficiently destroys the borate ester bonds of the ternary cross-linking system, promoting the rapid dissolution of the inner membrane layer. This avoids the problems of traditional protective membranes requiring manual cleaning, residual pollution, or incomplete self-dissolution hindering subsequent operations. It is especially suitable for scenarios that require automatic removal, such as temporary underwater protection and temporary protective layers on the surface of precision equipment. The outermost composite hydrophobic barrier layer has safe components, requires a small amount, and is easily degradable, avoiding the problems of traditional protective membrane materials being difficult to degrade and leaving residues that pollute the environment.
[0019] The preparation method of this application is simple and easy to operate, which is conducive to realizing continuous industrial production, improving production efficiency and reducing production costs.
[0020] The technical specifications of the self-dissolving protective membrane of this application are: tensile strength ≥25MPa, elongation at break ≥150%, swelling rate <5% after immersion in still water at 25℃ for 10 minutes with structural integrity, and trigger dissolution time ≤30s. The self-dissolving protective membrane of this application can be prefabricated as rolls or sheets and can be attached to the surface of water-related equipment such as deep-sea robots and offshore wind power foundations for underwater in-situ maintenance. Detailed Implementation
[0021] The present application will now be described in detail with reference to the embodiments.
[0022] Example 1 A method for preparing a self-dissolving protective membrane triggered under dual conditions in a water-contaminated environment includes the following steps: Polyvinyl alcohol with a degree of polymerization of 1800 and a degree of alcoholysis of 95% was dissolved in water at 85°C to prepare a 10wt% solution. Borax and boric acid were added to the polyvinyl alcohol solution at 60°C and stirred for 30-40 minutes to form a ternary reversible crosslinking system. The borate ester bond density in the ternary reversible crosslinking system was approximately 1.15 mmol / g. Borax accounted for 0.9wt% of the dry weight of polyvinyl alcohol, and boric acid accounted for 0.65wt% of the dry weight of polyvinyl alcohol. The molar ratio of borax to boric acid was approximately 1:1. Mechanically sensitive microcapsules were added to the ternary reversible crosslinking system, followed by ultrasonic dispersion and vacuum degassing to obtain a mixture; the mechanically sensitive microcapsules accounted for 5.5 wt% of the dry weight of polyvinyl alcohol (PVA). The microcapsules were prepared by in-situ polymerization. The capsule wall is a polyurea / polystyrene interpenetrating polymer network structure. The core is a citric acid-sodium citrate buffered decrosslinking agent with a pH of 4.5-6.5. The mass ratio of citric acid to sodium citrate in the decrosslinking agent is 1:1.5. The mixture is coated into a film and dried at 80°C for 10-20 minutes to obtain the inner film layer; A self-dissolving protective film is obtained by treating the dried inner membrane layer with a hydrophobic barrier. The hydrophobic barrier treatment is specifically formed by spraying a 5wt% silane-modified acrylic resin ethanol solution, followed by heat curing at 100℃ for 10 min. The thickness of the composite hydrophobic barrier layer after drying is approximately 2.0 μm.
[0023] The prepared self-dissolving protective membrane was tested for stability and trigger dissolution time under static water / salt water / cold water / simulated wave conditions in an environment of pH 6-9 to evaluate its biodegradability. The tensile strength and elongation at break of the self-dissolving protective membrane were measured using an electronic universal testing machine. The swelling rate was determined by gravimetric method: the weight of a dried membrane sheet was recorded as... After immersing in the test medium for a specified time, remove the sample, absorb the surface moisture, weigh it, and record the weight. The calculation formula is: The test results are as follows: Mechanical properties: tensile strength 28MPa, elongation at break 170%, good flexibility, easy to fit complex curved surfaces.
[0024] Static water stability: When the prepared self-dissolving protective membrane was placed in still water at 25°C, there was no significant swelling (swelling rate <2%) after 15 min, and the structure remained intact; there were no signs of dissolution within 1 hour, and the mechanically sensitive microcapsules did not rupture.
[0025] Cold water / salt water stability: When the prepared self-dissolving protective membrane was placed in 24℃ cold water / 35‰ saline, there was no significant swelling (swelling rate <2%) after 15 minutes, and the structure remained intact; there were no signs of dissolution within 1 hour, and the mechanically sensitive microcapsules did not rupture.
[0026] Simulated wave dynamics disturbance: To verify the anti-false triggering performance, the membrane material was placed in a wave-generating tank and subjected to continuous scouring at a flow velocity of 0.5 m / s and reciprocating oscillation at a frequency of 0.5-2.0 Hz and an amplitude of 50 mm (simulating ocean wave conditions). After 2 hours of continuous disturbance, the hydrophobic barrier layer effectively resisted water flow shear, no cracks appeared on the membrane surface, and no false triggering occurred in the microcapsules, proving that low-frequency hydrodynamics cannot activate the high-frequency response system designed in this application.
[0027] Dissolution triggering time: Directly applying a 110Hz vibration with an amplitude of 0.3mm to the self-dissolving protective membrane resulted in no significant change. However, after immersing the self-dissolving protective membrane in still water with a salinity of 35‰ at 25℃ for 24 hours (simulating long-term storage), applying a 110Hz vibration with an amplitude of 0.3mm effectively generated microcracks in the hydrophobic barrier layer, leading to complete dissolution within 10 seconds. The vibration was applied by contacting the vibration output end with the wall of the container holding the water (utilizing the water medium to conduct mechanical waves).
[0028] Biodegradability: Based on theoretical evaluation and raw material characteristic analysis, the dissolution products of this self-dissolving protective membrane are mainly polyvinyl alcohol (PVA) oligomers, borates and citrates. All components meet the OECD 301B standard for easy biodegradability. The biodegradability rate in aquatic environments is ≥90% after 28 days, with no risk of persistent microplastic residues.
[0029] The self-dissolving protective film in this embodiment balances stability, trigger sensitivity, and mechanical strength.
[0030] Example 2 A method for preparing a self-dissolving protective membrane triggered under dual conditions in a water-contaminated environment includes the following steps: Polyvinyl alcohol with a degree of polymerization of 2000 and a degree of alcoholysis of 99% was dissolved in water at 85°C to prepare a 12wt% solution. Borax and boric acid were added to the polyvinyl alcohol solution at 60°C and stirred for 30-40 minutes to form a ternary reversible crosslinking system. The borate ester bond density in the ternary reversible crosslinking system was approximately 1.4 mmol / g. Borax accounted for 1.1wt% of the dry weight of polyvinyl alcohol, and boric acid accounted for 0.9wt% of the dry weight of polyvinyl alcohol. The molar ratio of borax to boric acid was approximately 1:1.2. Mechanically sensitive microcapsules were added to the ternary reversible crosslinking system, followed by ultrasonic dispersion and vacuum degassing to obtain a mixture; the mechanically sensitive microcapsules accounted for 7.5 wt% of the dry weight of polyvinyl alcohol (PVA). The microcapsules were prepared by in-situ polymerization. The capsule wall is a polyurea / polystyrene interpenetrating polymer network structure. The core is a citric acid-sodium citrate buffered decrosslinking agent with a pH of 4.5-6.5. The mass ratio of citric acid to sodium citrate in the decrosslinking agent is 1:1.5. The mixture is coated into a film and dried at 80°C for 10-20 minutes to obtain the inner film layer; A self-dissolving protective film is obtained by treating the dried inner film layer with a hydrophobic barrier. Specifically, the hydrophobic barrier treatment is achieved by impregnating the film with an 8wt% paraffin-toluene solution containing 3wt% photoinitiator Irgacure2959 and a curing dose of 800 mJ / cm³. 2 After impregnation, it was placed in a light source with a main wavelength of 365nm and a light intensity of 80mW / cm². 2 The composite hydrophobic barrier layer is cured by irradiation under an LED ultraviolet light source for 10 seconds; the thickness of the dried layer is approximately 1.0 μm.
[0031] The performance test was conducted according to the method described in Example 1, and the results are as follows: Mechanical properties: tensile strength 32MPa, elongation at break 160%.
[0032] Static water stability: When the prepared self-dissolving protective membrane was placed in still water at 25°C, there was no significant swelling after 12 minutes, with a swelling rate of 2% and the structure remained intact; there were no signs of dissolution within 1 hour, and the mechanically sensitive microcapsules did not rupture.
[0033] Cold water / salt water stability: When the prepared self-dissolving protective membrane was placed in 24℃ cold water / 35‰ saline, there was no significant swelling (swelling rate <2%) after 15 minutes, and the structure remained intact; there were no signs of dissolution within 1 hour, and the mechanically sensitive microcapsules did not rupture.
[0034] Dissolution trigger time: Directly applying vibration at 110 Hz and 0.3 mm amplitude to the self-dissolving protective film resulted in no significant change. However, when the self-dissolving protective film was immersed in still water with a salinity of 35‰ and a temperature of 25℃ for 24 hours, it completely dissolved within 5 seconds under the influence of vibration at 110 Hz and 0.3 mm amplitude.
[0035] The simulated wave dynamics disturbance and biodegradability test results are consistent with those of Example 1.
[0036] The self-dissolving protective membrane formulation of this embodiment sacrifices a small amount of hydrostatic stability time in exchange for excellent mechanical strength and extremely fast trigger response, making it suitable for components that need to withstand water flow impact or require rapid maintenance.
[0037] Example 3 A method for preparing a self-dissolving protective membrane triggered under dual conditions in a water-contaminated environment includes the following steps: Polyvinyl alcohol with a degree of polymerization of 1700 and a degree of alcoholysis of 88% was dissolved in water at 85°C to prepare a solution with a concentration of 8.5 wt%. Borax and boric acid were added to the polyvinyl alcohol solution at 60°C and stirred for 30-40 min to form a ternary reversible crosslinking system. The borate ester bond density in the ternary reversible crosslinking system was approximately 0.9 mmol / g. Borax accounted for 0.7 wt% of the dry weight of polyvinyl alcohol, and boric acid accounted for 0.4 wt% of the dry weight of polyvinyl alcohol. The molar ratio of borax to boric acid was approximately 1:0.8. Mechanically sensitive microcapsules were added to the ternary reversible crosslinking system, followed by ultrasonic dispersion and vacuum degassing to obtain a mixture; the mechanically sensitive microcapsules accounted for 4 wt% of the dry weight of polyvinyl alcohol (PVA). The microcapsules were prepared by in-situ polymerization. The capsule wall was a polyurea / polystyrene interpenetrating polymer network. The core was a citric acid-sodium citrate buffered decrosslinking agent with a pH of 4.5-6.5. The mass ratio of citric acid to sodium citrate in the decrosslinking agent was 1:1.5. The mixture is coated into a film and dried at 80°C for 10-20 minutes to obtain the inner film layer; A self-dissolving protective film is obtained by treating the dried inner film layer with a hydrophobic barrier. The hydrophobic barrier treatment is specifically formed by spraying a 3wt% aqueous solution of fluorocarbon surfactant. After spraying, it is heat-cured at 80°C for 15 minutes. The performance test was conducted according to the method described in Example 1, and the results are as follows: Mechanical properties: tensile strength 26MPa, elongation at break 210%, extremely flexible, and has excellent fit.
[0038] Static water stability: When the prepared self-dissolving protective membrane was placed in still water at 25°C, there was no significant swelling after 10 minutes, and slight swelling after 60 minutes of immersion, with a swelling rate of about 4.5%; there were no signs of dissolution within 1 hour, and the mechanically sensitive microcapsules did not rupture.
[0039] Dissolution trigger time: Direct application of 110Hz vibration with an amplitude of 0.3mm to the self-dissolving protective membrane resulted in no significant change. When the self-dissolving protective membrane, after being immersed in still water with a salinity of 35‰ at 25℃ for 24 hours, was subjected to 110Hz vibration with an amplitude of 0.3mm, it completely dissolved within 16 seconds. Under extreme vibration testing (200Hz), there was a <3% probability of slight localized response, but it remained reliable within the specified frequency range.
[0040] The simulated wave dynamics disturbance and biodegradability test results are consistent with those of Example 1.
[0041] The self-dissolving protective film formulation in this embodiment reduces raw material costs while meeting basic technical requirements.
[0042] Comparative Example 1 This comparative example demonstrates the problems caused by excessively low crosslinking density by significantly reducing the amount of crosslinking agent used.
[0043] Compared to Example 1, the only difference is that in the ternary reversible crosslinking system, borax accounts for 0.5 wt% of the dry weight of polyvinyl alcohol, and boric acid accounts for 0.2 wt% of the dry weight of polyvinyl alcohol. The performance test was conducted according to the method described in Example 1, and the results are as follows: Mechanical properties: The film is sticky, has poor strength, and a tensile strength of only 8MPa, making it impossible to rewind and construct normally.
[0044] Static water stability: When the prepared self-dissolving protective membrane is placed in still water at 25°C, it begins to soften, expand and rupture within 2 minutes, failing to meet the basic requirement of 10 minutes.
[0045] In this comparative example, the protective film prepared in this example was too fragile to form effective structural support, leading to premature product failure. This comparative example demonstrates that even using the same low-cost process, insufficient crosslinking agent dosage cannot achieve the purpose of this application.
[0046] Comparative Example 2 This comparative example demonstrates the problems caused by excessively high crosslinking density by significantly increasing the amount of crosslinking agent used.
[0047] Compared to Example 1, the only difference is that in the ternary reversible crosslinking system, borax accounts for 1.3 wt% of the dry weight of polyvinyl alcohol, and boric acid accounts for 1.1 wt% of the dry weight of polyvinyl alcohol. The performance test was conducted according to the method described in Example 1, and the results are as follows: Mechanical properties: The film is hard and brittle, with an elongation at break of only 50%. It is prone to cracking when bent and cannot be wound up.
[0048] Static water stability: The prepared self-dissolving protective membrane was placed in still water at 25°C and showed no change after 30 minutes.
[0049] Dissolution trigger time: Directly applying vibration at 110 Hz and 0.3 mm amplitude to the self-dissolving protective membrane resulted in no significant change. However, when the self-dissolving protective membrane, after being immersed in still water with a salinity of 35‰ at 25℃ for 24 hours, was subjected to vibration at 110 Hz and 0.3 mm amplitude, the membrane only swelled and disintegrated into gel-like fragments, failing to completely dissolve within 30 seconds. In this comparative example, excessive cross-linking resulted in overly high network stability, indicating that the de-cross-linking agent released by the microcapsules was insufficient to completely destroy the overly dense cross-linked network, thus hindering rapid dissociation after triggering.
[0050] Comparative Example 3 In this comparative example, the mechanically sensitive microcapsules were excessively added.
[0051] Compared with Example 1, the only difference is that in the inner membrane layer, the mechanically sensitive microcapsules account for 9 wt% of the dry weight of polyvinyl alcohol (PVA).
[0052] The performance test was conducted according to the method described in Example 1, and the results are as follows: Mechanical properties: The material's internal properties are uneven due to excessive foreign phases, resulting in a decrease in strength to 15 MPa.
[0053] Static water stability: The large number of microcapsules, acting as defect points, disrupted the continuity of the cross-linked network, and the stability of the membrane in static water at 25°C decreased to about 6 minutes.
[0054] Dissolution triggering time: Directly applying vibration at 200 Hz and 0.3 mm amplitude to the self-dissolving protective membrane caused some microcapsules to rupture due to stress concentration, resulting in localized swelling points on the protective membrane, posing a significant risk of false triggering. Applying vibration at 110 Hz and 0.3 mm amplitude to the self-dissolving protective membrane, which had been immersed in still water with a salinity of 35‰ at 25℃ for 24 hours, resulted in complete dissolution of the membrane within 18 seconds.
[0055] This comparative example aims to illustrate that excessive addition of mechanosensitive microcapsules can sacrifice the integrity of the self-dissolving protective membrane and trigger reliability.
[0056] The test data of Examples 1-3 and Comparative Examples 1-3 are summarized in Table 1.
[0057] Table 1 Test data of Examples 1-3 and Comparative Examples 1-3
[0058] The above results show that Examples 1-3 all meet the expected technical indicators of this application, namely, tensile strength ≥25MPa, elongation at break ≥150%, swelling rate <5% after immersion in still water at 25℃ for 10min and structural integrity, and trigger dissolution time ≤30s.
[0059] Comparative Examples 1 and 2 show that the amount of crosslinking agent needs to be precisely controlled; too much or too little will lead to performance degradation. Comparative Example 3 shows that, since the mechanically sensitive capsule has a certain volume, it should be added in an appropriate amount; excessive addition will affect the mechanical properties and stability of the inner membrane layer.
[0060] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A self-dissolving protective membrane triggered under dual conditions in a water-contaminated environment, characterized in that: It includes an inner membrane layer and a composite hydrophobic barrier layer disposed on the inner membrane layer; The inner membrane layer comprises a dynamic cross-linked network and mechanosensitive microcapsules dispersed within the dynamic cross-linked network; the dynamic cross-linked network is a ternary reversible cross-linked system composed of polyvinyl alcohol, borax, and boric acid, with borax accounting for 0.6-1.2 wt% of the dry weight of polyvinyl alcohol and boric acid accounting for 0.3-1.0 wt% of the dry weight of polyvinyl alcohol; the mechanosensitive microcapsules have a particle size of 1-10 μm; the capsule wall thickness of the mechanosensitive microcapsules is 50-200 nm, and the glass transition temperature T0 is... g The temperature range is -10℃ to 10℃; the capsule wall of the mechanosensitive microcapsule is a polyurea / polystyrene interpenetrating polymer network structure, with a polyurea to polystyrene mass ratio of 1:1; the core of the mechanosensitive microcapsule is a citrate-sodium citrate buffered decrosslinking agent with a pH of 4.5-6.5; the amount of the mechanosensitive microcapsule added accounts for 3-8 wt% of the dry weight of polyvinyl alcohol; the inner membrane layer has a swelling rate of <5% in still water at 15-35℃ and can maintain structural integrity for more than 10 minutes in still water; The composite hydrophobic barrier layer is composed of a hydrophobic agent sprayed or impregnated on the membrane surface. The hydrophobic agent is selected from paraffin wax, silane-modified acrylic resin, or fluorocarbon surfactant. The composite hydrophobic barrier layer has a static water contact angle ≥110° and a thickness of 0.5-5μm. It can generate microcracks under mechanical vibration with a frequency of 50-200Hz and an amplitude ≥0.2mm to form water molecule permeation channels.
2. The self-dissolving protective membrane triggered under dual conditions in a water-related environment according to claim 1, characterized in that: The dynamic crosslinking network is based on polyvinyl alcohol with a degree of polymerization of 1700-2000 and a degree of hydrolysis of 88-99%, which is prepared into an 8-12 wt% aqueous solution and forms a ternary reversible crosslinking system with borax and boric acid.
3. The self-dissolving protective membrane triggered under dual conditions in a water-related environment according to claim 1, characterized in that: The borate ester bond density in the ternary reversible crosslinking system is 0.8-1.5 mmol / g; the molar ratio of borax to boric acid is 1:(0.5-2).
4. The self-dissolving protective membrane triggered under dual conditions in a water-related environment according to claim 1, characterized in that: The citric acid-sodium citrate buffered decrosslinking agent used as the core comprises an aqueous solution of citric acid and sodium citrate in a mass ratio of 1:(1.2-1.5).
5. The self-dissolving protective membrane triggered under dual conditions in a water-related environment according to claim 1, characterized in that: The total thickness of the self-dissolving protective film is 40-120 μm.
6. The self-dissolving protective membrane with dual-condition triggering in water-related environments according to claim 1, characterized in that: The mechanically sensitive microcapsules are prepared by in-situ polymerization; the composite hydrophobic barrier layer is subjected to thermosetting or ultraviolet curing treatment.
7. A method for preparing a self-dissolving protective membrane under dual-condition triggering in a water-related environment as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Polyvinyl alcohol is dissolved in water at 80-90℃ to prepare a solution with a concentration of 8-12wt%. At 55-65℃, borax and boric acid are added to a polyvinyl alcohol solution and stirred for 30-40 minutes to form a ternary reversible crosslinking system. Mechanically sensitive microcapsules were added to the ternary reversible crosslinking system, and the mixture was ultrasonically dispersed and then degassed under vacuum to obtain a mixture. The mixture is coated into a film and dried at 78-82℃ for 10-20 minutes to obtain the inner film layer. The dried inner membrane layer is subjected to a hydrophobic barrier treatment. The hydrophobic barrier treatment steps are as follows: spray or impregnate with a 5-10 wt% hydrophobic agent solution, and dry at 50-60℃ for 5-10 minutes to form a composite hydrophobic barrier layer. Finally, it is cured by thermosetting or UV curing.
Citation Information
Patent Citations
Endurable concrete additive
CN108947308A
Slow-release rust-inhibiting microcapsule applied to reinforced concrete and preparation method of slow-release rust-inhibiting microcapsule
CN120393876A
